2018
DOI: 10.1080/02699931.2018.1519497
|View full text |Cite
|
Sign up to set email alerts
|

Attention to faces and gaze-following in social anxiety: preliminary evidence from a naturalistic eye-tracking investigation

Abstract: Social attentional biases are a core component of social anxiety disorder, but research has not yet determined their direction due to methodological limitations. Here we present preliminary findings from a novel, dynamic eye-tracking paradigm allowing spatial-temporal measurement of attention and gaze-following, a mechanism previously unexplored in social anxiety. 105 participants took part, with those high (N = 27) and low (N = 25) in social anxiety traits (HSA and LSA respectively) entered into the analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
(124 reference statements)
2
11
2
Order By: Relevance
“…However, our data suggest that gaze-following is an attentional process that is unaffected by SA, even for expressions that could be perceived as threatening to high-SA participants (e.g., anger). Our findings align with those of Gregory et al (2019), who found that those with SA do not show differences in overt gaze-following behaviour compared with a control group; however, we have extended this finding to the gaze-cueing paradigm, which can capture covert shifts of attention. In showing that this lack of modulation extends to gaze cueing by angry expressions, for which a range of attentional biases in SA have been demonstrated (e.g., Mogg et al, 2004), we have also extended the findings of Gregory and Jackson (2017), Wei et al (2019), and Boll et al (2016), who used only neutral expressions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our data suggest that gaze-following is an attentional process that is unaffected by SA, even for expressions that could be perceived as threatening to high-SA participants (e.g., anger). Our findings align with those of Gregory et al (2019), who found that those with SA do not show differences in overt gaze-following behaviour compared with a control group; however, we have extended this finding to the gaze-cueing paradigm, which can capture covert shifts of attention. In showing that this lack of modulation extends to gaze cueing by angry expressions, for which a range of attentional biases in SA have been demonstrated (e.g., Mogg et al, 2004), we have also extended the findings of Gregory and Jackson (2017), Wei et al (2019), and Boll et al (2016), who used only neutral expressions.…”
Section: Discussionsupporting
confidence: 90%
“…However, these studies only employed gaze cues with neutral expressions; the lack of a socially threatening context could therefore explain the absence of any modulation. Recently, Gregory et al (2019) examined overt gaze following in a low-SA group and a high-SA group. These authors found no differences between the groups in the frequency of gaze-elicited eye movements, but again, only neutral expressions were used; furthermore, it is possible that differences might only manifest in covert attentional shifts (i.e., those occurring without eye movements), given that socially anxious individuals are especially conscious of how they appear to others (Hope & Heimberg, 1988).…”
mentioning
confidence: 99%
“…Importantly, this avoidance was only found during the actual performance of the speech. Not only are such findings consistent with previous public speaking studies conducted with community samples (Farabee et al, 1993;Lowe et al, 2012), but they are also in line with studies reporting no effects of social anxiety in community samples during face viewing (e.g., Berdica et al, 2018;Gregory et al, 2019;Mühlberger et al, 2008;Waechter et al, 2014). The findings extend previous research by providing direct evidence, within the same sample, that visual avoidance of faces in HSA persons depends on the type of social situation.…”
Section: Discussionsupporting
confidence: 91%
“…This evidence challenges previous studies showing that autistic participants use eye gaze similarly to typical individuals during a live Q&A task (Freeth & Bugembe, 2019; Vabalas & Freeth, 2016; Von dem Hagen & Bright, 2017 Experiment 2), or that they spend less time looking at a live confederate (Hessels et al, 2018; Von dem Hagen & Bright, 2017 Experiment 2). Interestingly, two recent studies have found that participants with high social anxiety traits look earlier and more to faces at the start of the interaction, compared to participants with low social anxiety traits (Gregory et al, 2019; Gutiérrez-García et al, 2019). The authors suggest that this attentional bias could reflect compensation strategies to anticipate negative evaluations.…”
Section: Discussionmentioning
confidence: 99%